2009
DOI: 10.2106/jbjs.h.01442
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and Fixed-Bearing (All-Polyethylene Tibial Component) Total Knee Arthroplasty Designs

Abstract: The two designs functioned equivalently at the time of early follow-up in this low-to-moderate-demand patient group. The rotating-platform design had no significant clinical advantage over the design with the all-polyethylene tibial component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 19 publications
5
56
1
6
Order By: Relevance
“…Our review showed improvement in mean Knee Society clinical and functional scores that parallel the results reported in studies that have not separated patients on the basis of patient age [1,2,6,8,12,19,27,30]. Although physician-generated scores suggest improvement, reporting biases that appear to overlook negative patient experiences were identified during this review, including minimizing the impact of revision procedures for patellar resurfacing, polyethylene wear, instability, and stiffness (Table 1).…”
Section: Discussionsupporting
confidence: 68%
“…Our review showed improvement in mean Knee Society clinical and functional scores that parallel the results reported in studies that have not separated patients on the basis of patient age [1,2,6,8,12,19,27,30]. Although physician-generated scores suggest improvement, reporting biases that appear to overlook negative patient experiences were identified during this review, including minimizing the impact of revision procedures for patellar resurfacing, polyethylene wear, instability, and stiffness (Table 1).…”
Section: Discussionsupporting
confidence: 68%
“…In a recent prospective randomized study comparing mobile and fixed TKA designs, Gioe et al [8] demonstrated no differences in the domains of clinical score, pain relief, or ROM. A recent meta-analysis of 33 studies assessing outcomes of 3532 TKAs [16] also suggested no difference in clinical or radiographic measures, such as clinical Knee Society score, clinical or functional American Knee Society score, ROM, activity, satisfaction, preference, radiographic alignment, osteolysis, wear, radiostereometric analysis measures, and complication rates between fixed-and mobile-bearing designs.…”
Section: Introductionmentioning
confidence: 98%
“…Very few studies have specifically compared fixed-bearing posterior-stabilized and mobile-bearing posterior-stabilized total knee prostheses. In a small number of studies, no differences in midterm functional and radiographic outcomes between patients with fixed and those with mobile-bearing posteriorstabilized prostheses were identified 4,11,12 . In one study with limited follow-up, implant survival rates were also reported to be similar 14 .…”
mentioning
confidence: 97%
“…It has also been argued that mobile bearings have the potential to enhance patellar tracking, reduce pain, enhance function, and reduce patellofemoral-related revision 8 . Many studies have compared clinical and radiographic outcomes of mobile and fixed-bearing total knee prostheses 4,5,7,[9][10][11][12] . One meta-analysis demonstrated an early reduction in anterior knee pain for patients with mobile-bearing total knee prostheses 7 .…”
mentioning
confidence: 99%